When Policies Fail. Challenges for Reducing Chronic Child Malnutrition in Ecuador - Manosalvas Vaca, Mónica Margarita (Revista del CLAD Reforma y Democracia, 2018)
On May 25, 2016, the government of Ecuador recognized that chronic child malnutrition was still a public problem for the country. After 7 years of an intervention to eradicate this phenomenon, not only the established goal was unfulfilled, but the speed at which chronic child malnutrition had been reduced until 2006 have decreased. What failed and how did this failure occur? This article seeks to answer these questions from the analysis of public policies approach. A qualitative methodology is followed and a case study is presented where the analytical technique is the pattern matching. The findings show that an interaction of the government’s legitimation objectives on the design of the public policy instruments helped to shape the failure.
Keywords: Public Policy; Policies Planning; Policies Implementation; Food Policy; Nutrition Policy; Children; Childhood; Ecuador